2017
DOI: 10.1136/bmjspcare-2016-001305
|View full text |Cite
|
Sign up to set email alerts
|

Sexual well-being in cancer and palliative care: an assessment of healthcare professionals’ current practice and training needs

Abstract: This survey identified that sexual well-being in cancer and palliative care patients is not routinely assessed with the majority of respondents stating that further support and training would be beneficial. The results of this questionnaire will be used to inform and develop sexual well-being training for HCPs working with cancer and palliative care patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 12 publications
0
5
0
1
Order By: Relevance
“…Finally, we found tension about how "the empowerment of the patient/partner" was concretely translated in the nurse-patient relationship by taking more of an initiating or waiting attitude towards conversations about sexual issues. This study demonstrates how the underlying discourse from a specific nursing area might interact with the nurses' concrete attitudes and behaviour, thereby offering a broader perspective on the results of other studies on this subject, studies that mainly focus on personal factors such as assumptions, values and comfort or discomfort in individual nurses (Gleeson & Hazell, 2017;Magnan & Reynolds, 2006;Reese et al, 2017).…”
Section: Discussionmentioning
confidence: 72%
“…Finally, we found tension about how "the empowerment of the patient/partner" was concretely translated in the nurse-patient relationship by taking more of an initiating or waiting attitude towards conversations about sexual issues. This study demonstrates how the underlying discourse from a specific nursing area might interact with the nurses' concrete attitudes and behaviour, thereby offering a broader perspective on the results of other studies on this subject, studies that mainly focus on personal factors such as assumptions, values and comfort or discomfort in individual nurses (Gleeson & Hazell, 2017;Magnan & Reynolds, 2006;Reese et al, 2017).…”
Section: Discussionmentioning
confidence: 72%
“…These patterns appear to be consistent across different clinical groups, as well as in primary care. Health care providers also often feel unequipped to deal with sexual issues and suggest there is a lack of resources to offer patients and their partners if they do identify a problem [13]. Despite the barriers identified, it has been reported that within a primary care setting, patients frequently identified that information related to sexual care should be routinely provided and that they would not object to clinicians initiating the discussion [14].…”
Section: Introductionmentioning
confidence: 99%
“…The most common reasons for non-assessment are fear, lack of knowledge about specialist services to which patients may be referred, and lack of access to assessment tools. Health professionals also indicated a need for support and training in this area [15,16]. Additionally, common reasons reported by medical staff were lack of time, prioritizing disease management over conversations about sexual health, or lack of understanding that adults in the final stages of chronic illness and in older age may still value their sexuality [7,[16][17][18].…”
Section: Discussionmentioning
confidence: 99%